ISOLATION OF 4CL1 GENE FROM PINUS MASSONIANA LAMB. IN VIETNAM - Huân, Hà Văn (Vietnam Journal of Biotechnology, 2011)
Lignin is a complex aromatic polymer of vascular plants that provides mechanical strength to the stem and protects cellulose fibres fi-om chemical and biological degradation. 4CL1 gene encoding 4-coumarate-CoA ligase, which play a key role in lignin biosynthesis pathway in plants. The fiiU-length cDNA of 4CL1 gene isolated firom Pinus massoniana Lamb, contains 1614 bp encoding 537 amino acid residues. We report on the cloning and sequencing of 4CL1 gene from secondary developing xylem tissues oi Pinus massoniana Lamb. Comparison of nucleotide sequences of 4CL1 gene firom Pinus taeda (Accession no., PTU12012) and Pinus massoniana Lamb, showed 98% similarity at nucleotide level and 99% at amino acid level. The nucleotide sequence of 4CL1 gene from Pinus massoniana Lamb, was deposited at NCBI database with the accession number FJ810495.